PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATIONTERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK - Muthia Diana Putri. (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts is one of the basic competence that should be developed by students. Mean while, in fact found that the understanding of mathematical concept of students grade VIII SMPN 24 Padang is still low. Team Assisted Individualization (TAI) type cooperative learning model can be solution to solve this problem. The purpose of this research is to know whether understanding of mathematical concept of student using cooperative learning TAI type is better that conventional learning in grade VIII of SMPN 24 Padang. The type of this research is quasy experiments, with static group design. The population in this research is students of grade VIII and the sample are VIII A as experiment class and VIII B as control class. Instrument that used is final test of understanding concepts. The result of this research shows that students understanding mathematical concept using TAI type of cooperative learning model is better than students understanding mathematical concepts using conventional learning.Keywords – understanding of mathematical concepts, cooperative learning model type Team Assisted Individualization, conventional learning.